Millimeter-Scaled Thick Cell Gap Measurement by Terahertz Spectroscopy Technology - Chao-Kuei Lee; Chung-Lun Wu; Han-Wei Zhang; Chun-Ta Wang; Tsung-Hsien Lin (IEEE Photonics Journal, 2016)
Cell gap thickness measurement on the scale of micrometers has been widely developed, due to its importance for applications such as display. In this paper, we propose and demonstrate a simple and precise method for measuring a millimeter-scaled cell gap by using a terahertz time-domain spectroscopy system. Basically, it is a kind of spectrum scanning method with a light source of broadband terahertz radiation. This method allows us to measure the cell gap from 15 $μ\text{m}$ to 1.5 mm. In addition, the accuracy of measured thickness for the proposed method is also discussed and analyzed. This is the first time, to our best knowledge, that we can precisely measure the cell gap thickness as high as millimeters by optical measurement.